Direito ambiental de conflitos: o direito ao meio ambiente ecologicamente equilibrado e os casos de colisão com outros direitos fundamentais - Dantas, Marcelo Buzaglo (2012)
Environmental law is a constitutional right and it frequently clashes with other protected rights. In these cases, differently from what happens to rule conflicts, in which, by the use of solution criterions, one of them is declared invalid, in competing principle cases, if harmonization is not possible, the solution is given by balancing, using the proportionality principle in its three dimensions (adequacy, necessity and strict proportionality), always through proper argumentation. There are some cases in which the proportionality test does not solve the conflict, and then judicial discretion appears. The object of this study is to analyze some situations where ecologically balanced environmental constitutional right clashes with others, such as cultural heritage, economic development, rule of law, res judicata, separation of powers, human dignity, living and traditional population rights in face of the creation of a protected area. The main target is to demonstrate that, since there are no absolute rights, in clash cases concerning ecologically balanced environmental right and other constitutional rights, if harmonization is not possible, any of them will prevail, according to the specificity of the case, as a result of balancing, using the proportionality principle and argumentation. The importance of this topic is immense because of its actuality and the fact that ecologically balanced environmental right is highly conflictive but, at the same time, very flexible, which stimulates practical agreement. The text was elaborated considering the most important issues that involve ecologically balanced environmental right, established by the Federal Constitution. It was searched, in specialized authors, the argumentation to demonstrate principles normative force and the technical solutions for hard cases, which, in a civil law tradition, means situations involving competing principles. In the end, specific situations in which environmental right clashes with other constitutional rights and the way Brazilian Courts have been solving these controversies were examined. The Supreme Court main decisions involving environmental issues were deeply analyzed. Polemic questions were brought to discussion, and different points of view about the controversy were shown. In order to clarify the analysis of some comparative law institutes, foreign references were brought, especially from the United States of America. The result was a systematization of a mostly complex and interesting topic, examined through actual doctrine and jurisprudence